HUBUNGAN VULVA HYGIENE DENGAN KECEPATAN PENYEMBUHAN LUKA PERINEUM DI TPMB Bd. DIENE SOFITASARI, S.Tr.Keb KOTA PROBOLINGGO: Vulva Hygiene with Speed of Healing Wounds at Independent Midwife Practice Diene Sofitasari, S.Tr.Keb Probolinggo - Dwi Setyo Rini (Forind Press, 2023)
Wounds on the perineum due to episiotomy, rupture or laceration are areas that are not easy to keep clean and dry. Perineal wound care for postpartum mothers is focused on reducing discomfort, maintaining cleanliness, preventing infection and increasing perineal wound healing. Vulva hygiene is cleaning the vulva area in women who have given birth up to 42 days postpartum. This study used Correlational analytical research design with the Cohort method. The population of all postpartum women who experienced perineal stitches at Independent Midwife Practice Diene Sofitasari, S.Tr.Keb Probolinggo as many as 30 postpartum mothers. The sampling method uses Total Sampling. The independent variable is vulva hygiene and the dependent variable is the speed of perineal wound healing in postpartum mothers. Research data obtained through a closed questionnaire. Data were tabulated and analyzed using the Chi-Square Test. The results showed that as many as 18 people (60%) did wrong vulva hygiene and as many as 20 people (66.7%) experienced slow healing of perineal wounds. The results of the study using the Chi-Square test showed p = 0.000, α = 0.05 p <α where H1 is accepted, meaning that there is a significant relationship between vulva hygiene and the speed of healing of perineal wounds in postpartum mothers. It is hoped that this research will increase the role of health workers in providing KIE with vulva hygiene in the healing of perineal wounds in postpartum women.